2022
DOI: 10.1016/j.heliyon.2022.e08806
|View full text |Cite
|
Sign up to set email alerts
|

The impact of COVID-19 on tertiary educational institutions and students in Bangladesh

Abstract: The COVID-19 forced to transform face-to-face mode of teaching to virtual in educational institutions around the globe that not only impact institutional stakeholders, but also posed as a threat to entire humanity because, all parties related to education had to change their activities. The intentions of this study therefore firstly, to determine the content analysis by interviewing tertiary students and secondly, to determine the frequency distribution by questionnaire developed from results of the content an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
15
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 37 publications
2
15
0
1
Order By: Relevance
“…Finally, this study also noticed an increasing (72%) psycho-logical disorders (anxiety=56.25%, stress=87.5%, depression=66%) among the students. Similar findings are also obtained in the following studies [31][32].…”
Section: Theme-5 Psychological Disordersupporting
confidence: 91%
“…Finally, this study also noticed an increasing (72%) psycho-logical disorders (anxiety=56.25%, stress=87.5%, depression=66%) among the students. Similar findings are also obtained in the following studies [31][32].…”
Section: Theme-5 Psychological Disordersupporting
confidence: 91%
“…Students also faced a financial crisis due to the pandemic, as they were required to rapidly transition to an online environment. A Bangladeshi study in tertiary education [86] found that 79% of (n=380) respondents faced financial difficulties hampering all intentions to purchase electronic devices and internet connection. 21% of respondents (n=107) borrowed their friends, relatives, or family members' electronic devices to carry out online activities and complete assignments [86].…”
Section: ) Socioeconomicmentioning
confidence: 99%
“…A Bangladeshi study in tertiary education [86] found that 79% of (n=380) respondents faced financial difficulties hampering all intentions to purchase electronic devices and internet connection. 21% of respondents (n=107) borrowed their friends, relatives, or family members' electronic devices to carry out online activities and complete assignments [86]. This income disparity is a testament to the effects of the digital divide, especially for those in developing countries.…”
Section: ) Socioeconomicmentioning
confidence: 99%
“…These contradictory findings suggest our understanding that there might be some additional factors which influence the relationship of TNL and IWB. Despite a negative tendency towards TNL, the outcomes of these leadership styles on IWB are still underexplored (Ryan & Tipu, 2013;Demesko 2017;Naqshbandi & Jasimuddin, 2018;Hosen, Uddin, Hossain, Islam, & Ahmad, 2022). Eliminating this issue, this study will examine the relationship between TNL and followers IWB is contingent on psychological empowerment (PE) of individual employees.…”
Section: Introductionmentioning
confidence: 99%